2019
DOI: 10.2478/slgr-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smartphones for Online Language Use in the Context of Polish and Croatian Students of Different Disciplines

Abstract: Easy and cheap access to the Internet and a wide array of new technologies, such as smartphones, have multiplied opportunities for online informal learning of English (OILE). Yet, despite sizeable research, few studies have examined the issue of OILE in the context of university students of different disciplines. The aim of this research study was to examine the role of online language use through smartphones among students of various disciplines and its possible effects on enhancement of their foreign languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Two productive and/or interactive online informal learning activities constitute nearly 100% of the participants under investigation. The two most frequently-performed productive and/or interactive online activities by EFL learners in Indonesia are writing short text messages and communicating with their classmates regarding study-related issues, which is in line with Jurkovič's (2019) finding in the Slovenian context and with Sierocka, Jurković, & Varga's (2019) finding in the context of Polish and Croatian students. Turning to the receptive ones, the online informal learning activities most frequently performed by the participants through their smartphones include looking for study-related information, accessing online dictionaries, listening to music, checking non-study related information, listening to lectures, reading social media comments, reading daily news and long texts, watching short clips with text, and reading emails.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Two productive and/or interactive online informal learning activities constitute nearly 100% of the participants under investigation. The two most frequently-performed productive and/or interactive online activities by EFL learners in Indonesia are writing short text messages and communicating with their classmates regarding study-related issues, which is in line with Jurkovič's (2019) finding in the Slovenian context and with Sierocka, Jurković, & Varga's (2019) finding in the context of Polish and Croatian students. Turning to the receptive ones, the online informal learning activities most frequently performed by the participants through their smartphones include looking for study-related information, accessing online dictionaries, listening to music, checking non-study related information, listening to lectures, reading social media comments, reading daily news and long texts, watching short clips with text, and reading emails.…”
Section: Discussionsupporting
confidence: 76%
“…Putrawan and Riadi (2020) who conducted preliminary research on the predominant language use for online learning activities found that English is not predominantly used by EFL learners in the Indonesian context. Sierocka, Jurković and Varga (2019) found that the subjects under their investigation use smartpones for receptive online activities more frequently, but they infrequently use their smartphones for the purpose of learning a language. They further stated that the predominant use of either first language or English for online informal learning activities does not significantly make an impact on the participants' self-assessed English competence.…”
Section: Literature Reviewmentioning
confidence: 96%
“…26 Sierocka et al (2019) Poland and Croatia "To examine the role of online language use through smartphones among students of various disciplines and its possible effects on enhancement of their foreign language skills" (p. 173).…”
Section: Taiwanmentioning
confidence: 99%